Factors impacting cerebrospinal fluid leak rates in endoscopic sellar surgery. Issue 11 (23rd August 2016) - Karnezis, Tom T.; Baker, Andrew B.; Soler, Zachary M.; Wise, Sarah K.; Rereddy, Shruthi K.; Patel, Zara M.; Oyesiku, Nelson M.; DelGaudio, John M.; Hadjipanayis, Constantinos G.; Woodworth, Bradford A.; Riley, Kristen O.; Lee, John; et al.
Abstract : Background: In patients undergoing transnasal endoscopic sellar surgery, an analysis of risk factors and predictors of intraoperative and postoperative cerebrospinal fluid leak (CSF) would provide important prognostic information. Methods: A retrospective review of patients undergoing endoscopic sellar surgery for pituitary adenomas or craniopharyngiomas between 2002 and 2014 at 7 international centers was performed. Demographic, comorbidity, and tumor characteristics were evaluated to determine the associations between intraoperative and postoperative CSF leaks. Correlations between reconstructive and CSF diversion techniques were associated with postoperative CSF leak rates. Odds ratios (OR) were identified using a multivariate logistic regression model. Results: Data were collected on 1108 pituitary adenomas and 53 craniopharyngiomas. Overall, 30.1% of patients had an intraoperative leak and 5.9% had a postoperative leak. Preoperative factors associated with increased intraoperative leaks were mild liver disease, craniopharyngioma, and extension into the anterior cranial fossa. In patients with intraoperative CSF leaks, postoperative leaks occurred in 10.3%, with a higher postoperative leak rate in craniopharyngiomas (20.8% vs 5.1% in pituitary adenomas). Once an intraoperative leak occurred, craniopharyngioma (OR = 4.255, p = 0.010) and higher body mass index (BMI) predicted postoperative leak (OR = 1.055, p = 0.010). In patients with an intraoperative leak, the use of septal flaps reduced the occurrence of postoperative leak (OR = 0.431, p = 0.027). Rigid reconstruction and CSF diversion techniques did not impact postoperative leak rates. Conclusion: Intraoperative CSF leaks can occur during endoscopic sellar surgery, especially in larger tumors or craniopharyngiomas. Once an intraoperative leak occurs, risk factors for postoperative leaks include craniopharyngiomas and higher BMI. Use of septal flaps decreases this risk.